2016
DOI: 10.1038/nchem.2643
|View full text |Cite
|
Sign up to set email alerts
|

Why copper is preferred over iron for oxygen activation and reduction in haem-copper oxidases

Abstract: Heme-copper oxidase (HCO) catalyzes the natural reduction of oxygen to water using a heme-copper center. Despite decades of research on HCO's, the role of nonheme metal and Nature's choice of copper over other metals like iron remains unclear. Here, we use a biosynthetic model of HCO in myoglobin that selectively binds different nonheme metals to demonstrate 30-fold and 11-fold enhancements in oxidase activity of Cu- and Fe-bound HCO mimics respectively, as compared to Zn-bound mimics. Detailed electrochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 55 publications
(46 reference statements)
2
135
0
Order By: Relevance
“…Most recently, Bhagi-Damodaran et al reported on a study which reflects on why nature may have chosen copper as the non-heme metal in the O 2 reduction site of heme-copper oxidases [238]. In constructs related to those mentioned above, an Mb was engineered to contain a non-heme 3-His-1-Glu binding pocket for Zn, Fe or Cu (Fig.…”
Section: Hetero-multinuclear Copper Active Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, Bhagi-Damodaran et al reported on a study which reflects on why nature may have chosen copper as the non-heme metal in the O 2 reduction site of heme-copper oxidases [238]. In constructs related to those mentioned above, an Mb was engineered to contain a non-heme 3-His-1-Glu binding pocket for Zn, Fe or Cu (Fig.…”
Section: Hetero-multinuclear Copper Active Sitesmentioning
confidence: 99%
“…The authors attributed this rate enhancement to the Cu ion center in Cu II -Fe B -Mb possessing a higher reduction potential relative to the non-heme Fe coordination moiety in Fe III -Fe B -Mb. This results in faster ET from an external reductant to the Cu ion within the hetero-binuclear center, corresponding to the overall rate-limiting step [238]. …”
Section: Hetero-multinuclear Copper Active Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Finally, the ability to encapsulate the metalloporphyin in artificial or engineered proteins has seen a recent surge in effort. 13-16 …”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have developed efficient nanocomposites that incorporate Cu and Ni as ORR catalysts. To the best of our knowledge, although Cu is not an active ORR catalyst compared to the most efficient non-noble materials, copper based enzymes are famous for their oxygen reduction reactivity [36][37][38][39]. On the other hand, the extensively-studied PtM (M is transition metal such as Ni, Fe, Co) [40][41][42] demonstrates enhanced kinetics of the ORR than the commercial Pt/C.…”
Section: Introductionmentioning
confidence: 99%